Advances in Chemical Crystallography: A Themed Issue Honoring Professor Alexandra M. Z. Slawin on the Occasion of Her 60th Birthday - Harrison, William T. A.; Aitken, R. Alan; Waddell, Paul (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
A compilation of papers presenting original research results in the areas of organic, inorganic, organometallic, solid state and theoretical chemistry with a common theme of the use of X-ray diffraction to solve chemical problems.